2009
DOI: 10.1002/btpr.291
|View full text |Cite
|
Sign up to set email alerts
|

A metal‐chelate affinity reverse micellar system for protein extraction

Abstract: A new nonionic reverse micellar system is developed by blending two nonionic surfactants, Triton X-45 and Span 80. At total surfactant concentrations lower than 60 mmol/L and molar fractions of Triton X-45 less than 0.6, thermodynamically stable reverse micelles of water content (W(0)) up to 30 are formed. Di(2-ethylhexyl) phosphoric acid (HDEHP; 1-2 mmol/L) is introduced into the system for chelating transition metal ions that have binding affinity for histidine-rich proteins. HDEHP exists in a dimeric form i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…One milliliter of supernatant was carefully collected into fresh vials and lyophilized to obtain a solid pellet. In the organic phase, the orientations of hydrophobic and hydrophilic segments are reversed to form reversed (25) and release the contents. Addition of dichloromethane reverses the MNF and release the drug in the surrounding organic environment.…”
Section: Entrapment and Loading Efficiencymentioning
confidence: 99%
“…One milliliter of supernatant was carefully collected into fresh vials and lyophilized to obtain a solid pellet. In the organic phase, the orientations of hydrophobic and hydrophilic segments are reversed to form reversed (25) and release the contents. Addition of dichloromethane reverses the MNF and release the drug in the surrounding organic environment.…”
Section: Entrapment and Loading Efficiencymentioning
confidence: 99%
“…19 The detailed studies have indicated that thermodynamically stable reverse micelles were formed with a mixture of Triton X-45 and Span 80 in n-hexane at total concentrations lower than 60 mmol/L and molar fractions of Triton X-45 less than 0.6. Characterization of the system indicated that 30 mmol/L of the surfactants at equimolar Triton X-45 and Span 80 had water content (the molar ratio of water to total surfactant concentration in the organic phase) of about 25 and gave high protein solubilization capacity.…”
Section: Nickel-chelate Reverse Micellesmentioning
confidence: 99%
“…The water content kept nearly unchanged at extensive pH values (3)(4)(5)(6)(7)(8)(9)(10)(11) and chelated metal concentration range. 19 Besides the nonionic surfactants, the organic phase contained 0 to 8 mmol/L sodium neutralized HDEHP (NaDEHP), which was prepared as described previously. 19 The organic phase was contacted by mixing with 50 mL of 50 mmol/L NiSO 4 in a 250-mL flask by reciprocal shaking in a water bath at 25 C for 60 min.…”
Section: Nickel-chelate Reverse Micellesmentioning
confidence: 99%
See 2 more Smart Citations